Associations between metabolic syndrome and erectile dysfunction: evidence from the NHANES 2001–2004 - Wei Wang; Wei Wang; Shuai Zhao; Ran Zhou; Ran Zhou; Pei-Ze Yu; Pei-Ze Yu; Si-Yuan Pan; Si-Yuan Pan; Peng-Fei Huan; Zhen-Duo Shi; Ying Liu; et al. (Frontiers in Public Health)
Background and objectivesErectile dysfunction is a common clinical condition that seriously affects the quality of life and mental health of men and their partners. Metabolic syndrome (MetS) is the most important public health problem threatening men’s health worldwide, and its current prevalence continues to grow. This study examines the relationship between metabolic syndrome and erectile dysfunction (ED).MethodWe conducted a cross-sectional study with data were sourced from NHANES 2001–2004. In this study, the relationship between METS-VF and ED was analyzed using multivariate logistic regression, followed by subgroup analyses to identify sensitive populations. Comparative logistic regression of the Receiver Operating Characteristic (ROC) curve assessed the diagnostic capability of METS-VF against the classical obesity index for ED. Creating Predictive Histograms for ED Patients and assess the net benefit of the model through Decision Curve Analysis (DCA).ResultsThe study enrolled 1,374 participants, of whom 545 self-reported ED history. There was a significant positive association between metabolic syndrome and erectile dysfunction (ED). The risk of ED in people with metabolic syndrome was 2.32 times higher than that in people without metabolic syndrome (dominance ratio = 2.32, 95% confidence interval: 1.83–2.96, p < 0.001). Subgroup analysis highlighted a stronger correlation in participants aged 50–85 years, hypertensive individuals, and those with large belly circumference. A histogram model including three variables: metabolic syndrome, age and smoking status was constructed to predict the probability of ED occurrence. And decision curve analysis (DCA) was used to assess the net benefit of its nomogram model at different high-risk thresholds. The high clinical utility of the model under different thresholds was illustrated.ConclusionThe risk of ED in people with metabolic syndrome was 2.32 times higher than that in people without metabolic syndrome. Furthermore, this observed positive correlation emphasizes the need for increased vigilance in patients with advanced age, smoking, and MetS.